Histological trends and molecular genetic features of non-small cell lung cancer in the Khanty-Mansiysk autonomous district – Ugra - A. A. Mordovskiy; A. A. Aksarin; A. M. Parsadanyan; P. P. Troyan; A. I. Pakhtusov (Сибирский онкологический журнал, 2024)
Objective: to study the histological structure of lung cancer, as well as molecular-genetic, gender, demographic and anamnestic characteristics of patients with non-small cell lung cancer in Khanty-Mansiysk Autonomous district – Ugra. Material and Methods. Material for the study consisted of 6725 cases of lung cancer for the period 2001–2020 and 266 cases diagnosed with non-small cell lung cancer for the period 2020–2023. Nonparametric Fisher’s criterion and χ2 test were used to analyze statistical factors. The relative risk of an event in the main group compared to the control group was calculated. Results. Squamous cell carcinoma remained the most common histological form among lung cancers detected for the periods 2001–2010 and 2011–2020 (40.2 and 38.3 %, respectively). During the second decade of the study period, the proportion of lung adenocarcinoma increased by 9.6%, approaching the rates of squamous cell lung carcinoma. It should be noted that in the structure of all histologic subtypes of non-small cell lung cancer, genetic aberrations occurred more frequently in adenocarcinoma than in other histologic forms of lung cancer (33 vs 6 %, respectively). The results of the analysis showed that the relative risk of developing genetic aberrations in EGFR, KRAS, ALK oncogenes was respectively 21.08; 9.04 and 10.84 times higher in lung adenocarcinoma and 15.87; 2.18 and 10.2 times higher among never smokers than in the control groups. The incidence of mutations in the EGFR gene was statistically more frequent in women (p<0.001), and the incidence of translocation in the AL K gene was predominantly diagnosed at age ≥48 years (p=0.002) regardless of gender. The specificity of PD-L1 expression levels (low – 63.2 %, medium – 16.2 %, high – 4.5 %) is consistent with other recent studies. Conclusion. The study of molecular-genetic changes observed in patients with non-small-cell lung cancer in Ugra allows the development of organizational and methodological approaches to diagnosis and treatment of these patients.